Dynamic Characteristics of Warm Mix Foamed Asphalt Mixture in Seasonal Frozen Area. (5th February 2019) - Hou, Yun; Cai, Yanxia; Zang, Zhishu; Qian, Zhenyu; Zhao, Bin
Abstract : In order to study dynamic characteristics of warm mix foamed asphalt mixture in seasonal frozen area, cylinder dynamic modulus test of four kinds of mixture with two gradations and three kinds of asphalt was carried out by UTM-100. Then, the effects of test temperature, loading frequency, and foaming water consumption on dynamic modulus were analyzed. Finally, the compressive resilient modulus trial was made to compare mechanical properties. Results show that dynamic modulus for warm mix foamed asphalt mixture increases with rising temperature and decreased frequency. The inflection points of the dynamic modulus vs frequency curves at low temperature, normal temperature, and high temperature are 2 Hz, 10 Hz, and 15 Hz, respectively. Static modulus of SBS# modified and nonmodified warm mix foamed asphalt mixture is corresponding to the dynamic modulus 0.001 Hz–0.1 Hz and 0.00001 Hz–0.05 Hz. The effect on gradation type on the dynamic modulus of asphalt mixture is AC-20 > AC-13, and the degree of sensitivity of the water consumption to the master curve equation of dynamic modulus under different gradations is AC-13 > AC-20.